Dive Into The Implication Of The Great Mandate In The Teaching Of Christian Religious Education Today - Hendrik Legi; Arip Surpi Sitompul (Jurnal Pendidikan Agama Kristen (JUPAK), 2023)
In the context of Christian education, education has a central role in shaping Christian character and encouraging students to implement the Great Commission in their actions and behavior. The Christian education approach covers various aspects, including the formation of Christian character, understanding values such as love and caring, spreading God's Word, motivation for service and giving, and pastoral spiritual aspects of students. Christian education also motivates students to carry out service and giving as an expression of Christ's love for fellow human beings. Thus, students learn to reflect on values such as forgiveness, honesty, and compassion in the context of service. The importance of spreading God's Word in Christian education includes a deep understanding of the message of God's Word and how it is relevant in everyday life. Students are taught to understand the teachings of Christianity in a spiritual context and apply them in their lives, including in their decisions and actions. It includes the development of a personal relationship with God, an understanding of spiritual vocations, and character development that reflects the values of Christianity. Spiritual guidance and deepening understanding of Christian teachings are integral in shepherding the spiritual aspects of students. Thus, Christian education has a great responsibility in shaping Christian character, understanding the values of Christianity, and shepherding the spiritual aspects of students. Through this holistic approach, Christian education helps students carry out the Great Commission in their actions and behaviors, making them beneficial citizens of society as well as staunch followers of Christian religious values.